UPAYA TERUKUR PENINGKATAN KINERJA DENGAN PENGUATAN DISIPLIN DAN PEMBERIAN MOTIVASI KERJA PADA KARYAWAN PT. SEWU SEGAR PRIMATAMA JAKARTA - Hira Maulida (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study was to determine the effect of work discipline and motivation on employee performance at the Tangerang City National Defense Office. either partially or simultaneously. The method used in this research is a quantitative method. The sampling technique used is saturated sampling, using a sample of 60 respondents. The data analysis technique used is statistical analysis by testing the validity test, reliability test, classic assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of work discipline research have a significant effect on employee performance partially, indicated by the simple linear regression equation Y = 12.403 + 0.706 X1. This is evidenced by the hypothesis test obtained tcount > ttable (3.469 > 2.000) and reinforced by the ? value < Sig.0.05 or significance <0.05 (0.000 <0.05). Motivation has a significant effect on employee performance partially as shown by the simple linear regression equation Y = 15.412 + 0.637 X2. This is evidenced by the results of the hypothesis testing obtained tcount > ttable (3.395 > 2.000) and reinforced by the ? value < Sig.0 .05 or a significance value <0.05 (0.000 <0.05). The results of work discipline and motivation research on employee performance at the Tangerang City National Defense Office are shown by the multiple linear regression equation Y = 7.884 + 0.431 X1 + 0.383 X2 This is evidenced by the simultaneous hypothesis test results obtained by the value of fcount > ftable ( 33.599> 3.16) and reinforced by a significance value <0.05 (0.000 <0.05). The test results for the coefficient of determination of work discipline (X1) and motivation (X2) have an effect of 54.1% on the performance of employees at the Tangerang City National Defense Office. Thus H0 isrejected and H3is accepted. This means that it is proven that there is a significant effect simultaneously between work discipline (X1) and motivation (X2) on employee performance (Y).